Impact of public reporting on the quality of hospital care in Germany: A controlled before–after analysis based on secondary data. Issue 7 (July 2016) - Kraska, Rike Antje; Krummenauer, Frank; Geraedts, Max
Highlights: Public reporting of hospitals in Germany stimulated immediate and accelerated quality improvement. This effect seems to be independent of hospitals' profit orientation. Only indicators with sufficient improvement potential should be reported. To exploit the effect, reportable quality indicators should be replaced on a regular basis. Abstract: Background: Since 2005 all German hospitals are obliged to publish structured quality reports (QR). International studies suggest that mandatory reporting motivates hospitals to improve the quality of care. We examine whether such an effect can be demonstrated for hospitals in Germany and whether differences exist between for-profit and non-profit hospitals. Method: The study was designed as a controlled pre-post intervention study, whereby the intervention consisted in the first notification of the obligation to publish values for clinical quality indicators (QI). The data basis consisted of those QI reported in identical manner from 2006 to 2012 and multivariable statistical analyses were performed. QI from the same clinical area but without reporting obligation in 2006, served as control group. Results: Six QI were included in the intervention group and demonstrated significant quality improvement. The major part of improvements occurred immediately after the intervention. 31 QI were included in the control group, with about 60% showing improvement trends. In comparison, the biggest proportional improvements were registered for publicly reported QI. No significant differences in relation to profit orientation were found. Conclusion: Results indicate a positive effect of public reporting on hospital care, independent of a hospital's profit orientation. Improvements in the quality of care were registered for all observed QI over time, but public reporting stimulated an accelerated QI improvement.